Mapping the design and implementation of seed sector regulation: The case of Rwanda - Kuhlmann, Katrin; Nalinya, Adron Naggayi; Spielman, David J.; Francis, Tara (International Food Policy Research Institute, 2025)
Rwanda’s seed sector is changing, with clear signs of a move towards greater responsiveness to market actors and forces and new investments in the production and distribution of improved varieties and quality seed to farmers. This study examines how the country’s legal and regulatory systems support—or constrain—the development and delivery of improved varieties and quality seed in light of these changes. Using a Regulatory Systems Mapping (RSM) approach, the study assesses four core areas of Rwanda’s seed sector: variety registration and release, early generation seed (EGS) production and distribution, seed quality assurance, and seed trade. The analysis integrates stakeholder perspectives from across the public and private sectors, highlighting critical implementation bottlenecks, institutional coordination gaps, and areas where laws diverge from practice. Findings show that while Rwanda has made significant strides in advancing a market-oriented vision for its seed sector and aligning with regional frameworks such as the Common Market for Eastern and Southern Africa (COMESA), systemic issues persist, including limited clarity on appeals processes, underdeveloped quality control infrastructure, and insufficient support for private sector breeding and farmer-based enterprises. The study offers targeted, time-bound recommendations for improving regulatory effectiveness, promoting inclusive participation (especially by women and farmer groups), and operationalizing flexibilities that suit Rwanda’s seed sector. By focusing on both regulatory design and implementation realities, this work aims to support ongoing policy reform and investment efforts in Rwanda’s seed sector.